Survey of chiropractic clinicians on self-reported knowledge and recognition of concussion injuries - David N. Taylor; Shari Wynd (Chiropractic & Manual Therapies, 2018)
Abstract Background There has been little study of the recognition of mild traumatic brain injury (MTBI) by the chiropractic practitioner, or of the inquiry by the clinician to assess those patients who may be suffering from the condition, but fail to report the symptoms. Although severe cases of TBI are more often recognized and treated by attendance to hospital or emergency room, MTBI is less recognizable and would present a long-term risk to the patient. Given the clinical risk associated with failure to recognize such injuries, training of the clinician in the subtle signs of MTBI is imperative. What we currently know about training in the recognition of MTBI is from limited recent knowledge based studies. This study is intended to assess the self-reported mild traumatic brain injury (MTBI) knowledge, recognition and treatment by chiropractic practitioners. Methods A previously published standardized set of survey items was distributed to a captive audience of chiropractic practitioners at the July 2016 Texas Chiropractic College annual symposium. The sample population was a convenience sample of chiropractic clinicians who were assessed for MTBI knowledge and common practices. Results There was a response rate of 43% of the 125 attendees. The survey demonstrated confidence in MTBI diagnosis. Average MTBI knowledge and recognition score was only 27% ± 22%. Frequency of MTBI patients presenting to the chiropractic clinician office was an average of less than one per month. Sixty nine percent (69%) of the clinicians relied upon their history and clinical exam for diagnosis. There was no knowledge of the Balance Error Scoring system and only 20% utilized the Standardized Concussion Assessment Tool (SCAT). The primary action of the chiropractic clinician who suspected MTBI was to refer to a neurological specialist (76%). A small minority of practitioners would provide treatment. Conclusions There is an overconfidence of the chiropractic practitioner in recognition of MTBI which is incongruent with the low knowledge scores. Further education of the chiropractic clinician is warranted. Trial registration University Hospital Medical Information Network Clinical Trials Registry. Retrospectively registered (UMIN-CTR), trial number: UMIN#000029744 (Receipt# R000033980) data: October 27, 2017.​Date of enrollment 7/14/2016.